Diverging temporal trends in stroke incidence in younger vs older people: A systematic review and meta-analysis - Scott, CA; Li, L; Rothwell, PM (American Medical Association, 2022)
Importance: Overall stroke incidence is falling in high-income countries, but data on time trends in incidence of young stroke (ie, stroke in individuals younger than 55 years) are conflicting. An age-specific divergence in incidence, with less favorable trends at younger vs older ages, might be a more consistent underlying finding across studies. Objective: To compare temporal trends in incidence of stroke at younger vs older ages in high-income countries. Data Sources: PubMed and EMBASE were searched from inception to February 2022. One additional population-based study (Oxford Vascular Study) was also included. Study Selection: Studies reporting age-specific stroke incidence in high-income countries at more than 1 time point. Data Extraction and Synthesis: For all retrieved studies, 2 authors independently reviewed the full text against the inclusion criteria to establish their eligibility. Meta-analysis was performed with the inverse variance–weighted random-effects model. Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) reporting guideline was followed. Main Outcomes and Measures: The main outcome was age-specific divergence (<55 vs ≥55 years) in temporal trends in stroke incidence (relative temporal rate ratio [RTTR]) in studies extending to at least 2000. RTTRs were calculated for each study and pooled by random-effects meta-analysis, with stratification by administrative vs prospective population-based methodology, sex, stroke subtype (ischemic vs intracerebral hemorrhage vs subarachnoid hemorrhage) and geographical region. Results: Among 50 studies in 20 countries, 26 (13 prospective population-based and 13 administrative studies) reported data allowing calculation of the RTTR for stroke incidence at younger vs older ages across 2 or more periods, the latest extending beyond 2000. Reported trends in absolute incidence of young individuals with stroke were heterogeneous, but all studies showed a less favorable trend in incidence at younger vs older ages (pooled RTTR = 1.57 [95% CI, 1.42-1.74]). The overall RTTR was consistent by stroke subtype (ischemic, 1.62 [95% CI, 1.44-1.83]; intracerebral hemorrhage, 1.32 [95% CI, 0.91-1.92]; subarachnoid hemorrhage, 1.54 [95% CI, 1.00-2.35]); and by sex (men, 1.46 [95% CI, 1.34-1.60]; women, 1.41 [95% CI, 1.28-1.55]) but was greater in studies reporting trends solely after 2000 (1.51 [95% CI, 1.30-1.70]) vs solely before (1.18 [95% CI, 1.12-1.24]) and was highest in population-based studies in which the most recent reported period of ascertainment started after 2010 (1.87 [95% CI, 1.55-2.27]). Conclusions and Relevance: Temporal trends in stroke incidence are diverging by age in high-income countries, with less favorable trends at younger vs older ages, highlighting the urgent need to better understand etiology and prevention of stroke at younger ages.